2018
DOI: 10.1038/s41598-018-29113-2
|View full text |Cite
|
Sign up to set email alerts
|

Differential profiling of lacrimal cytokines in patients suffering from thyroid-associated orbitopathy

Abstract: The aim was to investigate the levels of cytokines and soluble IL-6R in the tears of patients with thyroid-associated orbitopathy (TAO) disease. Schirmer’s test was adopted to collect tears from TAO patients (N = 20, 17 women, mean age (±SD): 46.0 years (±13.4)) and healthy subjects (N = 18, 10 women, 45.4 years (±18.7)). Lacrimal cytokines and soluble IL-6R (sIL-6R) were measured using a 10-plex panel (Meso Scale Discovery Company) and Invitrogen Human sIL-6R Elisa kit, respectively. Tear levels of IL-10, IL-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 80 publications
2
24
0
Order By: Relevance
“…Clinical studies have reported that tears of dry eye patients show increased levels of IL-1α and mature IL-1β which correlated to corneal fluorescein staining ( 42 , 48 , 65 ). Similar increased levels of inflammatory cytokines have also been reported in active TAO patients indicating that measurement of tear cytokine levels might be a useful diagnostic tool in multiple ocular inflammatory conditions ( 54 , 55 ).…”
Section: Tearssupporting
confidence: 68%
See 2 more Smart Citations
“…Clinical studies have reported that tears of dry eye patients show increased levels of IL-1α and mature IL-1β which correlated to corneal fluorescein staining ( 42 , 48 , 65 ). Similar increased levels of inflammatory cytokines have also been reported in active TAO patients indicating that measurement of tear cytokine levels might be a useful diagnostic tool in multiple ocular inflammatory conditions ( 54 , 55 ).…”
Section: Tearssupporting
confidence: 68%
“…Many of the same studies and other groups have also shown elevated levels of tumor necrosis factor-alpha (TNF-α) which is thought to represent a measure of the general inflammatory status of the ocular surface in sub-sets of DED ( 48 , 51 , 58 ). TNF-α has also been shown to be significantly higher in tears from TAO patients when compared to controls ( 54 , 55 ). The proinflammatory cytokine Interleukin-1 (IL-1) which includes two forms- Interleukin-1alpha (IL-1α) and Interleukin-1beta (IL-1β) has been detected in human tear fluid ( 39 , 64 ).…”
Section: Tearsmentioning
confidence: 99%
See 1 more Smart Citation
“…Rationale and Mechanisms of Action. The level of tumor necrosis factor alpha (TNFα) was found to be elevated in the serum [51], tears [52], and orbital tissues [53] of GO patients compared to controls. TNFα stimulated the expression of adhesion molecules and hyaluronan production in orbital fibroblasts, but these actions were inhibited by anti-TNFα agents [54].…”
Section: Anti-tumor Necrosis Factor Alpha Therapymentioning
confidence: 99%
“…Higher serum levels of IL-6 were noted in GD patients with GO than in those without GO [73]. Greater lacrimal levels of IL-6 were also shown in GO patients compared to healthy controls, and they positively correlated with CAS [52,74]. Therefore, blocking the IL-6 pathway by tocilizumab (TCZ), a fully human IgG1 anti-IL-6 receptor monoclonal antibody, represents a sound strategy in GO.…”
Section: Tocilizumabmentioning
confidence: 99%